The Effect of Capital Intensity Ratio and Sales Growth to Tax Avoidance with Independent Commissioners as Moderating Variable (Empirical Study on Consumer Goods Industry Companies on the Indonesia Stock Exchange in 2021-2022): English - Hasna, Fadhilah; Zulaihati, Sri; Sumiati, Ati (Nexus Synergy: A Business Perspective, 2023)
This study aims to: 1) determine the effect of capital intensity ratio and sales growth to tax avoidance; (2) regarding the effect of capital intensity ratio to tax avoidance; (3) the effect of sales growth to tax avoidance; (4) the effect of capital intensity to tax avoidance with the moderating of independent commissioners; and (5) the effect of sales growth to tax avoidance. the population in this study are consumer good industry listed on the Indonesia Stock Exchange in the 2021-2022 period. The source of data in this study is the annual report data of the consumer goods industry companies. The proxied of the variable are cash effective tax rate for tax avoidance, capital intensity ratio, sales growth rate, and the proportion of independent commissioners of the companies. The sampling method used was purposive sampling and 65 companies were selected with a total sample of 170 research data. The analytical technique used are multiple linear regression and moderated regression analysis. Data is processed using SPSS. The results of the study indicate that capital intensity and sales growth have a significant effect on tax avoidance, capital intensity has a positive effect on tax avoidance, sales growth has no significant effect on tax avoidance,  independent commissioners is able to strengthen the effect of capital intensity on tax avoidance, meanwhile the independent commissioners are unable to moderate the effect of sales growth on tax avoidance.